2015
DOI: 10.1097/bco.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data confirm clinical trial outcomes for rivaroxaban in orthopaedic patients

Abstract: Venous thromboembolism (VTE) is a potential cause of morbidity and mortality in patients after major orthopaedic surgery. Based on the results of the international phase III RECORD (Regulation of Coagulation in Orthopaedic Surgery to Prevent Deep Vein Thrombosis and Pulmonary Embolism) program, the oral, direct Factor Xa inhibitor rivaroxaban has been approved in many countries for the prevention of VTE after elective hip arthroplasty or knee arthroplasty. However, study results of randomized controlled trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Some systematic reviews have demonstrated that there was no difference in the incidence of major bleeding between rivaroxaban and enoxaparin and that rivaroxaban was more beneficial than enoxaparin for decreasing the risk of VTE. However, most of those reviews included only favorable rivaroxaban dosage 17 18 19 20 21 22 or studies that reported phase III trials 23 24 . For these reasons, we conducted this systematic review and meta-analysis to further explicate the benefits and harms of rivaroxaban for thromboprophylaxis after THA or TKA.…”
mentioning
confidence: 99%
“…Some systematic reviews have demonstrated that there was no difference in the incidence of major bleeding between rivaroxaban and enoxaparin and that rivaroxaban was more beneficial than enoxaparin for decreasing the risk of VTE. However, most of those reviews included only favorable rivaroxaban dosage 17 18 19 20 21 22 or studies that reported phase III trials 23 24 . For these reasons, we conducted this systematic review and meta-analysis to further explicate the benefits and harms of rivaroxaban for thromboprophylaxis after THA or TKA.…”
mentioning
confidence: 99%